Time to death predictors of HIV/AIDS infected patients on antiretroviral therapy in Ethiopia - Tadege, Melaku (BMC Res Notes, 2018)
OBJECTIVE: The purpose of this study was to identify the major risk factors, which contributed to shortened survival time to death of HIV patients on antiretroviral therapy. Six-hundred HIV patients were included from two hospitals and six health centers record from January 2003 to December 2017. Kaplan–Meier and Cox proportional hazard model were implemented. RESULTS: From the Kaplan–Meier, log-rank test result indicated that there was a significant difference between tuberculosis comorbidity (P = .000), occupation (P = .027), and WHO clinical stage (P = .012) on the survival experience of patients at 5% statistical significance level. From the Cox regression result, the risk of death for patients who lived with tuberculosis was about 2.872-fold times higher than those patients who were negative. Most of the HIV/AIDS patients on antiretroviral therapy were died in a short period due to tuberculosis comorbidity, began with lower amount of CD4, being underweight, merchant, and being on WHO clinical stage IV. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-018-3863-y) contains supplementary material, which is available to authorized users.